2013
DOI: 10.1111/j.1476-8070.2013.01734.x
|View full text |Cite
|
Sign up to set email alerts
|

A Chaotic Intervention: Creativity and Peer Learning in Design Education

Abstract: Peer feedback and critique is integral to the creative practice of studio‐based textile designers. In a creative learning context, how do students perceive the role of peer feedback and critique? What conditions do students identify as being important to stimulating creativity in a collaborative peer feedback and critique‐driven learning environment? This article highlights research conducted in one undergraduate textile design programme of an urban Australian university based on a small‐scale designed learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Among these are the role of educational technology and human capital (Viaene & Zilcha, 2009), the issue of competence development (Velasco (2014), knowledge regimes in relation to education reforms (Aasen et al, 2014), issues of creativity and peer learning (Budge et al, 2013), human capital and knowledge spillovers (Schumacher et al, 2014), and human capital spillovers in families (Kuziemko (2014). The explored issues constitute a fairly rich spectrum and represent a body of economics and business-related educational research worthy of further scrutiny, extension, and expansion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among these are the role of educational technology and human capital (Viaene & Zilcha, 2009), the issue of competence development (Velasco (2014), knowledge regimes in relation to education reforms (Aasen et al, 2014), issues of creativity and peer learning (Budge et al, 2013), human capital and knowledge spillovers (Schumacher et al, 2014), and human capital spillovers in families (Kuziemko (2014). The explored issues constitute a fairly rich spectrum and represent a body of economics and business-related educational research worthy of further scrutiny, extension, and expansion.…”
mentioning
confidence: 99%
“…Among these are Barlas, Diker, and Polat (1997); Barlas and Diker (2000); Hazlett (2000); De Fraja (2002); Marginson (2007); Kara (2007;2013) ;Viaene and Zilcha (2009) ;Loomis and Rodrigues (2009) ;Eckwert and Zilcha (2012); Budge, Beale, and Lynas (2013); Velasco (2014); Aasen, Proitz, and Sandberg (2014) ;Schumacher, Dias, and Tebaldi (2014); and Kuziemko (2014).…”
mentioning
confidence: 99%
“…But even though design reviews did not happen often, it was observed that during the presentation students were highly motivated to make comments and suggestions about each other´s work. The diversity of thinking in class reflects previous research on creativity, studio learning, and social constructivism learning 8,10,27 .…”
Section: Discussionmentioning
confidence: 99%
“…In the studio model, it is also common for students to participate in critique sessions that provide them with different points of view and considerations that must then be judged and applied if considered helpful, in an iterative process 26,27 . This stimulates critical thinking, another desired trait for learners in today's society 1,2,5,28 .…”
Section: Studio Environmentmentioning
confidence: 99%
See 1 more Smart Citation